POTENSI EKSTRAK KULIT SEMANGKA UNTUK MENINGKATKAN SISTEM IMUNITAS IKAN KOI (Cyprinus carpio L) TERHADAP SERANGAN Aeromonas hydrophila - Nyoman Distanaya (Clarias : Jurnal Perikanan Air Tawar, 2023)
This research aimed to determine the effective concentration of watermelon rind extract for enhancing koi fish immune system which attacked by Aeromonas hydrophila bacteria. Completely Randomize Design Experiment is used as base research method who has five treatments and three replications. The treatment have been given addition of watermelon rind extract in feed with concentration which are A (0 ppm), B (6.250 ppm), C (7.500 ppm), D (8.250 ppm) and E (9.000 ppm). The observed parameters are clinical symptoms, total leucocyte, survival rate, and water quality. The result of this research indicated that the addition of watermelon rind extract in feed with the amount of concetration between 8.250 until 9.000 ppm could enhancing fish immune system and prevent Aeromonas hydrophila bacteria infection, this could be showed by the enhanced amount of leucocytes are 49,24 and 55,96%, and the highest survival rate shows 84,44% and 71% value respectively.